TVDI as an indicator of water status in spring-summer crops in Rio Grande do Sul State, Brazil - Schirmbeck, Lucimara Wolfarth; Fontana, Denise Cybis; Schirmbeck, Juliano (Agrometeoros, 2018)
This work aimed at evaluating the TVDI (Temperature-Vegetation Dryness Index) as an indicator of water status and characterizing water spatial and temporal variability for the spring-summer crops in Rio Grande do Sul. For this purpose, the surface temperature MODIS products (MOD11A2) and vegetation index (MOD13A2) with spatial resolution of 1,000 m and temporal resolution of 8 and 16 days, respectively, were used to obtain the TVDI. Data from meteorological stations were also used to determine the water balance. The period of analysis corresponded to the spring-summer crops of 2011-12, 2012-13, 2013-14, 2014-15 and 2015-16. The results show that the TVDI is a good indicator of water surface status and represented well the water deficit occurrence in the spring-summer crops. The spatial and temporal resolution of the images used to calculate the index allowed obtaining reliable data, both during the development cycle and between Ecoclimatic Regions. These characteristics show that TVDI can be used as an indicator of water status and can, therefore, be part of the agrometeorological monitoring programs in Rio Grande do Sul.